Transcatheter tricuspid annuloplasty with band implantation and its safety profile: a single-center experience. (3rd October 2022) - Martinez Moya, R R; Ortega Perez, R; Pardo Sanz, A; Salido Tahoces, L; Sanchez Recalde, A; Abellas Sequeiros, M; Mestre Barcelo, J L; Fernandez Golfin, C; Garcia Martin, A; Hinojar Baydes, R; Rivas Garcia, S; Manjon Rubio, H; et al.
Abstract: Introduction: Severe tricuspid regurgitation is a prevalent valve disease with a negative impact on the prognosis and quality of life of patients. Transcatheter tricuspid annuloplasty with band implantation is an alternative for the treatment of this pathology in patients with high surgical risk. Due to the recent development of this device, data regarding its safety are scarce. The objective of this study was to describe the adverse events and complications related to transcatheter tricuspid annuloplasty with band implantation in our center in order to assess its safety. Methods: In a series of 27 patients, the incidence of adverse events related to the procedure was analysed, considering death, stroke, myocardial infarction (MI), bleeding complications (extensive or life-threatening), vascular complications (pseudoaneurism), coronary complications, device-related secondary intervention (DRSI), device-related cardiac surgery (DRCS), renal failure (RF) or conduction system disturbance (CSD). Likewise, the incidence of death and hospitalizations due to heart failure in a 15-month follow-up was evaluated. Results: No deaths, stroke, MI, DRCS, RF or CSD were recorded in relation with the percutaneous band implantation. There was 1 (3.7%) bleeding related to femoral venous vascular access that required suture and compression for 30 minutes. Development of 1 (3.7%) pseudoaneurysm was observed which was resolved with ultrasound-guided thrombin injection and 2 (7.4%) perforations of the right coronary artery (1 requiring stent implantation and another one self-limited without flow compromise). There was 1 (3.7%) patient with failed band implantation and eventual percutaneous bicaval prosthesis implantation was required. After a follow-up of 15 months, 2 (7.4%) deaths from non-cardiological causes (exacerbation of chronic obstructive pulmonary disease and traumatic brain injury) and 3 (11.1%) admissions due to decompensated heart failure were documented. Conclusion: Transcatheter tricuspid annuloplasty with band implantation appears to be a safe technique with a low incidence of complications for treating patients with severe tricuspide regurgitation and high surgical risk. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Gobierno de España